PsycEXTRA Dataset 2012
DOI: 10.1037/e685842012-132
|View full text |Cite
|
Sign up to set email alerts
|

Parietal Contributions to Visual Working Memory Depend on Task Difficulty

Abstract: The nature of parietal contributions to working memory (WM) remain poorly understood but of considerable interest. We previously reported that posterior parietal damage selectively impaired WM probed by recognition (Berryhill and Olson, 2008a). Recent studies provided support using a neuromodulatory technique, transcranial direct current stimulation (tDCS) applied to the right parietal cortex (P4). These studies confirmed parietal involvement in WM because parietal tDCS altered WM performance: anodal current t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 96 publications
1
14
0
Order By: Relevance
“…This type of interaction between brain stimulation and cognitive load has only previously been reported in the context of working memory, to the authors’ knowledge (Jones & Berryhill, ; Sandrini et al ., ; Wu et al ., ). For example, using an oppositional montage, Sandrini et al .…”
Section: Discussionmentioning
confidence: 98%
“…This type of interaction between brain stimulation and cognitive load has only previously been reported in the context of working memory, to the authors’ knowledge (Jones & Berryhill, ; Sandrini et al ., ; Wu et al ., ). For example, using an oppositional montage, Sandrini et al .…”
Section: Discussionmentioning
confidence: 98%
“…A relationship between cognitive brain state and stimulation effects is also suggested by the small number of behavioral studies which demonstrate that manipulations of task difficulty can influence the behavioral modulations seen with tDCS (Gill, Shah‐Basak, & Hamilton, ; Jones & Berryhill, ; Li et al, ; Sandrini, Fertonani, Cohen, & Miniussi, ; Wu et al, ). Transcranial alternating current stimulation also shows effects on cortical network activity and connectivity that are dependent on the cognitive brain state (Neuling, Rach, Herrmann, & Schwiedrzik, ; Violante et al, ; Vosskuhl, Huster, & Herrmann, ).…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that the DLPFC might be more involved in modulating behavior when the participants had to resolve cognitively demanding problems. Previous studies have shown that the effects of tDCS over parietal cortex (Jones & Berryhill, ) or over the DLPFC (Gill et al ., ) were related to the difficulty of the cognitive tasks.…”
Section: Discussionmentioning
confidence: 99%